The Implementation of Islamic Entrepreneurship Education to Build Independence and Responsible Character in Students (Santri) at Islamic Boarding Schools - Syarofina Idzni Lucksha; Rahmawati Baharuddin (Indonesian Journal of Character Education Studies, 2025)
Background: Islamic boarding schools often teach entrepreneurship alongside religious studies, yet the concrete linkage between entrepreneurial practice and character formation is not always explicit or systematically documented. Objective: To determine how Islamic entrepreneurship education shapes independent and responsible character among santri in Islamic boarding schools. Method: Descriptive qualitative research conducted in 2024 at Manager Tholabie Islamic Boarding School, Buring, Malang. Data were collected through observation, interviews, and documentation. Credibility was ensured via triangulation of sources and techniques. Data analysis followed four stages: data collection, data reduction, data display, and conclusion drawing/verification. Result: Entrepreneurship instruction is deliberately connected to religious knowledge and delivered through an integrated curriculum. This alignment embeds entrepreneurial practice in daily religious learning and school routines, fostering santri independence and responsibility. Conclusion: A values-aligned, curriculum-integrated model of Islamic entrepreneurship education effectively cultivates independent and responsible character in the pesantren context. Contribution: The study clarifies how religious values and entrepreneurial practice can be operationally integrated at the levels of curriculum, pedagogy, and institutional routines, and highlights practical design elements that educators can replicate to strengthen character outcomes.